1978
DOI: 10.1055/s-0028-1097470
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Components of Styrax officinalis L. – IV1

Abstract: The structure of styraxin, a lignan from Styrax officinalis, has been established as 2-exo-(3',4'-methylenedioxyphenyl) 6-exo-(3"-methoxy, 4"-hydro-xypheny1)-4-0x0-3,7-dioxabicyclo-(3,3, 0) octane. MS and NMR spectral evidence as well as the results of X-ray crystallographic analysis are presented. styraxin, whose structure elucidation is presented in this communication. Previous work on the seeds of this plant resulted in the isolation and structure determination of two saponins [I, 2, 31 and a new benzofuran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
1
4
0
3
Order By: Relevance
“…As estruturas destas substâncias foram elucidadas a partir dos dados obtidos por análises espectroscópicas de RMN 1 H e 13 [20][21][22] . Análise dos espectros de RMN de 1 H e 13 C permitiram identificar a estrutura do triterpeno 2 como o ácido ursólico 23,24 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…As estruturas destas substâncias foram elucidadas a partir dos dados obtidos por análises espectroscópicas de RMN 1 H e 13 [20][21][22] . Análise dos espectros de RMN de 1 H e 13 C permitiram identificar a estrutura do triterpeno 2 como o ácido ursólico 23,24 .…”
Section: Resultsunclassified
“…Pesquisa bibliográfica sobre a constituição química de Styracaceae revelou a presença marcante de arilpropanóides monoméricos, lignóides [6][7][8][9][10][11][12][13][14][15] e triterpenóides [15][16][17][18] . O gênero Styrax , o mais importante da família e com maior volume de informações, caracteriza-se pelo acúmulo de norlignóides do tipo benzofurânicos, uma vez que os mesmos foram isolados em todas as espécies do gênero investigadas até o momento .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…1a and 1b). As far as we know, since its characterisation by Ulubelen et al [42] in the aerial parts of S. officinalis, styraxin 42 has not been reported to occur in other Styrax species and in any other plants. Hence, styraxin 42 could represent a specific marker of S. officinalis and could be used as an indicator for the use of S. officinalis resin in an archaeological context, as attested by its identification in an 8000 years-old decorated skull [16].…”
Section: Lignan and Neolignan Derivatives In Aromatic Balsamsmentioning
confidence: 93%
“…A species, Penstemon deustus, which belongs to the Family Scrophulariaceae contains a furofuranoid lignan liriodendrin which can be used as a cytotoxic agent (11). Styraxin, another a furofuran lignan, isolated from Styrax officinalis (Styraxaceae), also has antitumour activity (12). In 1989 Trumm and Eich reported that the two benzylbutyrolactones, arctigenin and trachelogenin, showed strong cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%